مسؤولية القاصر بين المسؤولية المحدودة والمسؤولية غير المحدودة في شركة التضامن. - حلوش, فاطمة امال; رفاس, محمد أمين (University of Eloued جامعة الوادي, 2020)
تعتبر مسؤولية الشركاء في شركات التضامن مسؤولية تضامنية وغير محدودة، وبالتالي يكتسب الجميع فيها صفة التاجر، وهو ما يمنع القاصر من الانضمام لهذا النوع من الشركات، إذ أن من شأن وجود شريك قاصر فيها تعريض أمواله للضياع، ولكن قد يتوفى الشريك المتضامن ويذر من بعده وريث قاصر، الأمر الذي يحتم على المشرع وضع نظام قانوني خاص يتماشى مع الخصوصية التي يتمتع بها القاصر، وذلك لبسط الحماية لأمواله، وهذا ما سيتم التطرق إليه في هذه الورقة البحثية.The responsibility of the partners in the solidarity companies is considered a solidarity and unlimited responsibility, and consequently, everyone gains the status of the trader, which prevents the minor from being a cleaner company for this type of company, as a minor partner may cause his money to be lost, but the supporting partner may die and become a minor heir. This makes it necessary for the legislator to establish a special legal system that is compatible with the privacy of the minor, in order to extend the protection of his money, which will be addressed in this paper
The responsibility of a minor between limited liability and unlimited liability in partnership companies
مقال
Keywords: تضامن ; شركة ; القاصر ; غير المحدودة ; المسؤولية; solidarity; company; minor; unlimited; responsibility.